Impact of progesterone concentration on human chorionic gonadotropin trigger day on clinical outcomes with one top-quality cleavage-stage embryo or blastocyst transfer in fresh in vitro fertilization cycles - Xu, Jianing; Zhang, Cuilian; Wang, Shuna; Zhang, Shaodi (Frontiers in Endocrinology, 2023)
Objective: To investigate the impact of the progesterone concentration on the human chorionic gonadotropin (hCG) trigger day on clinical outcomes with an antagonist protocol. Methods： The retrospective cohort study included a total of 1,550 fresh autologous ART cycles with one top-quality embryo transfer. Multivariate regression analysis, curve fitting, and threshold effect analysis were performed. Results: A significant association was found between the progesterone concentration and clinical pregnancy rate (adjusted OR, 0.77; 95% CI, 0.62–0.97; P = 0.0234), especially in blastocyst transfer (adjusted OR, 0.56; 95% CI, 0.39–0.78; P = 0.0008). The association between the progesterone concentration and the ongoing pregnancy rate was insignificant. The clinical pregnancy rate showed a linear relationship with an increased progesterone concentration in cleavage-stage embryo transfer. In blastocyst transfer, as the progesterone concentration increased, the clinical and ongoing pregnancy rates showed a parabolic reverse-U curve; the curve initially increased before declining at high progesterone concentrations. The clinical pregnancy rate increased with a progesterone concentration up to 0.80 ng/mL rather than tended to be stable. The clinical pregnancy rate significantly decreased when the progesterone concentration was ≥0.80 ng/mL. Conclusions: The progesterone concentration on the hCG trigger day exhibits a curvilinear relationship with pregnancy outcomes in blastocyst transfer cycles, and the optimal threshold of the progesterone concentration is 0.80 ng/mL.